New, Improved Version of the mCOP-PCR Screening System for Detection of Spinal Muscular Atrophy Gene (SMN1) Deletion - SHINOHARA, MASAKAZU (Kobe J Med Sci, 2017)
BACKGROUND: Spinal muscular atrophy (SMA) is a frequent autosomal recessive disorder, characterized by lower motor neuron loss in the spinal cord. More than 95% of SMA patients show homozygous survival motor neuron 1 (SMN1) deletion. We previously developed a screening system for SMN1 deletion based on a modified competitive oligonucleotide priming-PCR (mCOP-PCR) technique. However, non-specific amplification products were observed with mCOP-PCR, which might lead to erroneous interpretation of the screening results. AIM: To establish an improved version of the mCOP-PCR screening system without non-specific amplification. METHODS: DNA samples were assayed using a new version of the mCOP-PCR screening system. DNA samples had already been genotyped by PCR-restriction fragment length polymorphism (PCR-RFLP), showing the presence or absence of SMN1 exon 7. The new mCOP-PCR method contained a targeted pre-amplification step of the region, including an SMN1-specific nucleotide, prior to the mCOP-PCR step. mCOP-PCR products were electrophoresed on agarose gels. RESULTS: No non-specific amplification products were detected in electrophoresis gels with the new mCOP-PCR screening system. CONCLUSION: An additional targeted pre-amplification step eliminated non-specific amplification from mCOP-PCR screening.